2009
DOI: 10.1007/s11089-009-0199-5
|View full text |Cite
|
Sign up to set email alerts
|

Korean Pastors and Their Wives’ Marital Satisfaction and Its Predicting Factors

Abstract: This study examined to what extent Korean pastors and their wives in America were satisfied with their marital lives. It also investigated how selected factors predicted marital satisfaction among Korean pastors and their wives: communication, expression of affection, empathy, sexual satisfaction, and doing things together. Eighty-five pastors and 79 pastors' wives (n=164) participated in this study, and they were separately measured. The Kansas Marital Satisfaction Scale (KMSS) and Lee's Marital Inventory (LM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Results indicated that Chinese American couples were fluid in negotiating between these two categories of marriage harmony. Hyun and Shin (2010) examined various interpersonal variables in marriage satisfaction ratings. A sample of Korean pastors and their spouses were surveyed, and results indicated that expression of affection was an important predictor of marital satisfaction for both partners.…”
Section: Resultsmentioning
confidence: 99%
“…Results indicated that Chinese American couples were fluid in negotiating between these two categories of marriage harmony. Hyun and Shin (2010) examined various interpersonal variables in marriage satisfaction ratings. A sample of Korean pastors and their spouses were surveyed, and results indicated that expression of affection was an important predictor of marital satisfaction for both partners.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have been conducted to determine the factors that affect the quality of marriage and marital satisfaction (i.e. Hyun & Shin, 2010;Litzinger & Gordon, 2005;Schneewind, 2002). Various studies have also consistently found that communication, conflict resolution, and joint leisure time have a positive relationship with marital satisfaction (Hill, 1988;Holman & Jacquart, 1988;Orthner, 1975;Litzinger & Gordon, 2005).…”
Section: Strengthening Marital Relationships As a Pillar Of Co-parentingmentioning
confidence: 99%
“…In establishing interpersonal relationships, including marital relationships, it cannot be separated from conflict. In the early days of marriage, conflict is usually caused by an adaptation process that the couple faces where they have to face new responsibilities and face the realities of married life (Hyun and Shin, 2009), emotional stress and disputes caused by the adjustment and adaptation process ( Toomey, 2002), or facing various developmental and change tasks (Toomey, 2002). Furthermore, in Indonesia itself, during the early years of marriage, several conditions may differ from the state of the marital relationship in Western countries, and it can cause different conflicts in Indonesian marriage.…”
Section: Introductionmentioning
confidence: 99%